The Bacterial Pneumonia Characteristics based on Climate and Meteorological Parameters in Indonesia, the Tropical Country: A Preliminary Study - Bramantono Bramantono; Brian Eka Rachman; Erika Marfiani; Neneng Dewi Kurniati; Muhammad Vitanata Arifijanto; Tuksin Jearanaiwitayakul (Biomolecular and Health Science Journal, 2021)
Introduction: As a tropical country, Indonesia has the potential to influence the characteristics of infectious diseases. The purpose of this study was to see how the pattern of pneumonia on various weather components such as rainfall, humidity, and temperature.Methods: This study was carried by retrospective screening in the infectious ward in one of the tertiary referral hospitals.Results: A total of 876 cases of pneumonia from eight treatment rooms were included in the study. The highest pneumonia cases occurred in February with 239 (27.2%) cases followed in April and May with 169 (19.2%) and 159 (18.2%) cases respectively. After microbiological examination, bacterial growth was found in 191 cases. The highest number of bacteria was found in February with 62 (32%), followed by May with 33 (17.2%) and April with 31 (16.2%) samples. Most of the bacterial grown were gram-negative (94.3%), dominated by Klebsiella pneumoniae (35%), followed by Acinetobacter baumanii 17.2%  and Pseudomonas aeruginosa  12%. On the examination of antibiotic sensitivity, it was found that amikacin has a consistently high sensitivity (90%) for pneumonia caused by most bacterial causes (Acinetobacter baumanii, Klebsiella pneumoniae, and Escherichia coli).Conclusion: The study did not show any remarkable bacterial patterns based on weather components such as rainfall, humidity, and temperature during the rainy season. However, increasing the surveillance period will provide a better insight into the bacterial pattern and can compare it in the rainy and dry seasons.